PENGEMBANGAN MEDIA BELAJAR PECAHAN MENGGUNAKAN KARTU DOMINO UNTUK MENINGKATKAN LITERASI MATEMATIKA PADA ANAK KELAS IV SEKOLAH DASAR - Tsuraya Fitriani, Kamilia; Kusuma, Dani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research was conducted to improve the mathematical literacy of fourth grade students. The purpose of this development research is to describe the steps of media development, media validity, practicality, and media effectiveness. The development method used is the ADDIE development model. The results showed that the media that had been developed were effective for improving students' mathematical literacy. This is evidenced from the results of material validation obtained a score of 69.33% in the category quite feasible and the results of media validation obtained a score of 97.33% in the category very feasible. Practicality results seen from the response of students get a score of 82% with a good category and a teacher response of 94% with a good category. Effectiveness results through the t test obtained a sig value. 0.000 and the average pretest result of 46.5 and the average posttest result of 75. The results of the Ngain calculation to see the effectiveness of the media obtained a value of 25.00 in the very high category. Thus, the results of the products that have been developed in the form of fractions worth domino cards can be categorized as good and suitable for use in the learning process.